Penggunaan Bahasa Indonesia dalam Media Radio - Siti Putri Aprilia (Lembaga Pengembangan Kinerja Dosen, 2024)
Language is a system of arbitrary spoken symbols used by members of a language community to communicate and interact, based on the culture they share. Nowadays, communication facilities are increasingly sophisticated, but many people have not forgotten radio, even though many say it is outdated. It is not uncommon for many people to still use radio as a communication medium. Radio has a very big role in communication between humans. This research uses qualitative methods which aim to analyze the use of Indonesian in radio media. The results of this research show that the use of Indonesian in radio media has a significant impact on the effectiveness of communication and interaction between broadcasters and listeners. Mistakes in using Indonesian can result in confusion or wrong interpretation, thus interfering with understanding the message conveyed. Therefore, it is important for radio announcers to use Indonesian correctly and appropriately so that the message conveyed can be well understood by listeners.